PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN METODE INQUIRY BASED LEARNING DI SEKOLAH DASAR - Lu’luil Maknun; Lufi Haryanti (Jurnal Ilmiah Global Education, 2022)
This study aims to: 1. To apply inquiry based learning learning methods to Indonesian language subjects in elementary schools, especially in the current 21st century technology era, 2. To improve student achievement in the 21st century technology era, 3. Train students so that they are ready and able to adapt themselves in learning along with the times. This research is qualitative in nature by using the literature study method, namely data collection techniques by reviewing various sources of books, notes, literature, and various kinds of reports related to the theme. The results obtained in this study are that the inquiry learning learning model can be implemented by good in learning Indonesian in elementary school. The inquiry learning model is very effective and efficient to be applied in Indonesian language learning, where this inquiry learning model uses a student centered approach so that students are trained to think critically, creatively, and innovatively and the teacher is only a facilitator for their students, so it can be concluded that the method Inquiry based learning is very effective and efficient to apply in Indonesian language learning and can also be applied to other subjects, especially in the current 21st century technology era.